Intestinal bile acid receptors are key regulators of glucose homeostasis. Issue 3 (16th November 2017) - Trabelsi, Mohamed-Sami; Lestavel, Sophie; Staels, Bart; Collet, Xavier
Abstract : In addition to their well-known function as dietary lipid detergents, bile acids have emerged as important signalling molecules that regulate energy homeostasis. Recent studies have highlighted that disrupted bile acid metabolism is associated with metabolism disorders such as dyslipidaemia, intestinal chronic inflammatory diseases and obesity. In particular, type 2 diabetes (T2D) is associated with quantitative and qualitative modifications in bile acid metabolism. Bile acids bind and modulate the activity of transmembrane and nuclear receptors (NR). Among these receptors, the G-protein-coupled bile acid receptor 1 (TGR5) and the NR farnesoid X receptor (FXR) are implicated in the regulation of bile acid, lipid, glucose and energy homeostasis. The role of these receptors in the intestine in energy metabolism regulation has been recently highlighted. More precisely, recent studies have shown that FXR is important for glucose homeostasis in particular in metabolic disorders such as T2D and obesity. This review highlights the growing importance of the bile acid receptors TGR5 and FXR in the intestine as key regulators of glucose metabolism and their potential as therapeutic targets.